2015
DOI: 10.1007/s10921-015-0280-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Specimen Velocity on the Leakage Signal in Magnetic Flux Leakage Type Nondestructive Testing

Abstract: We investigate the influence of the specimen velocity on the magnetic flux leakage with the aim of selecting the optimum sensor locations. Parametric numerical simulations where the specimen velocity was in the range [0.1-20] m·s −1 were carried out. As the specimen velocity is increased, the magnetic field varies from being symmetrical to being asymmetric. For the radial magnetic induction, the peak to peak value moves from the centre of the bridge towards the direction of the specimen movement. For the axial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…As an emphasis on the effect of speed on MFL measurements, Figure 7 shows a recent study that attempts to optimize the capture of defect-induced MFL as the tool moves at different speeds relative to the pipe wall. 50 External factors such as residual magnetism in the pipe wall, the pipe material, and the pipe pressure also affect the MFL readings. The strength of the applied magnetic field should also be adjusted based on the pipe wall, with thick walls requiring stronger fields in order to reach full saturation.…”
Section: Electrical Phenomenamentioning
confidence: 99%
See 1 more Smart Citation
“…As an emphasis on the effect of speed on MFL measurements, Figure 7 shows a recent study that attempts to optimize the capture of defect-induced MFL as the tool moves at different speeds relative to the pipe wall. 50 External factors such as residual magnetism in the pipe wall, the pipe material, and the pipe pressure also affect the MFL readings. The strength of the applied magnetic field should also be adjusted based on the pipe wall, with thick walls requiring stronger fields in order to reach full saturation.…”
Section: Electrical Phenomenamentioning
confidence: 99%
“…As an emphasis on the effect of speed on MFL measurements, Figure 7 shows a recent study that attempts to optimize the capture of defect-induced MFL as the tool moves at different speeds relative to the pipe wall. 50…”
Section: Sensing Strategies For Subsea Pipeline Shmmentioning
confidence: 99%
“…One can define two different approaches to solve this problem. First approach involves optimization of an MFL tool in order to minimize the velocity influence on the MFL signal [11]. Second approach is based on post-processing and transformation of the signal to its stationary form.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that signals obtained for the aforementioned components are distorted by the scanning velocity [2][3][4]. As a result, an estimation of flaw dimensions is less accurate.…”
Section: Introductionmentioning
confidence: 99%
“…Most of them are based on a proper signal processing leading to restoration of the static form of the signal [4][5][6]. Other method assumes optimization of an MFL tool design in order to minimize the velocity impact [3]. In this work, another approach was proposed.…”
Section: Introductionmentioning
confidence: 99%